Ionizing Radiation Effects in Mos Oxides (International Series on Advances in Solid State Electronics and Technology - Oldham Timothy R (World Scientific, 2000)
This volume is intended to serve as an updated critical guide to the extensive literature on the basic physical mechanisms controlling the radiation and reliability responses of MOS oxides. There has been a significant amount of work on the nature of the electrically active defects in MOS oxides which are generated by exposure to ionizing radiation. These same defects are also critical in many other areas of oxide reliability research. As a result of this work, the understanding of the basic physical mechanisms has evolved. The book summarizes the new work and integrates it with older work to form a unified picture. It is aimed primarily at specialists working on radiation effects and oxide reliability.